CCL22 to activate Treg migration and suppress depigmentation in vitiligo - Eby, Jonathan M. (J Invest Dermatol, 2015)
In vitiligo, gradual cutaneous depigmentation and cytotoxic T cell activity against melanocytes is accompanied by a paucity of regulatory T cells (Tregs) in vitiligo patient skin, indicating that autoimmune responses are not adequately held in check. Thus we sought a means to repopulate patient skin with Tregs. We hypothesized that enhanced expression of CCL22 can promote Treg skin homing to suppress depigmentation. The mouse Ccl22 gene was cloned into an expression vector and resulting DNA was used for gene gun treatment. Two spontaneous depigmentation models with different kinetics of melanocyte loss were utilized, expressing tyrosinase-reactive and gp100-reactive T cell receptor transgenes. Mice were subjected to 5 gene gun treatments 6 days apart, scanned for depigmentation weekly thereafter and monitored for activation and proliferation of relevant T cells and for Treg infiltration to the skin. Significantly reduced depigmentation 2 weeks after treatment was accompanied by a markedly increased abundance of Tregs in the skin at the expense of melanocyte reactive, TCR transgenic T cells as well as by reduced proliferation and reduced IFN-γ production in response to cognate peptide. Continued treatment may be necessary for sustained, local immunosuppression. These findings suggest that topical CCL22 may be used for the treatment of vitiligo.